Comportamiento agronómico de maracuyá amarillo Passiflora edulis f. flavicarpa, en condiciones ambientales de sabana inundable, municipio de Arauca (2005)
In Arauca (flood plain), Colombia, between June 2006 and December 2007, a crop of yellow passion fruit was established; set up at 3.5 m between plants and furrows; a simple supporting plant structure with high beds was used,along with irrigated fertilization (on field A) and soil fertilization (on field B). Diameter of the stem, internodes length, number of tertiary guides, flowering start and flower opening were evaluated, as well as pollinators, flowerfruit/plant, production and plant health. 8 MAS (months after sowing), the diameter of the stem increased to 2.45 cm in field A, and 1.98 cm in field B. The length of internodes (vertical axis 2 m.) was 14 cm and 12.5 cm in field A and B respectively. The tertiary guides (horizontal axis 3.5 m), averaged 20.9 guides, with 65.95 flowers and 24.04 fruit/plant in field A, and 19.9 guides with 48.35 flowers and 23.3 fruits / plant in field B.Flowering started 5 MAS, in 22.4% of field A and 8.6% in field B, with floral opening between 11:00 and 11:30 am, entomophilically pollinated by Xylocopa sp, reduced by Apis mellifera bees, and ripening of fruits happening from 40 to 48 days after the pollination. The production recorded 7 MAS, evaluating the first 30 days of production, in field A was 90 kg with an average fruit weight of 152.33 g and field B, 83.6 kg and average fruit weight of 148 g.Regarding plant health, the disease found to be the one that affected the field the most, in environmental conditions of the municipality of Arauca at “El Cairo”, was Alternaria passiflorae, registering a peak incidence (IA) from 19.4%in field A and 12.9% for field B. This attack reduced production in field A, since it was the first to enter production and more fruits were exposed to the disease.Cladosporium herbarum recorded a peak incidence (Ic) of 41.8% and 41.9% for field A and B respectively. The most significant insect plague to the cultivation was Dione Juno, howeve / En el municipio de Arauca (sabana inundable), Colombia, entre Junio de 2006 y Diciembre de 2007, se evaluó un cultivo de maracuyá amarillo,establecido a 3.5m entre plantas y surcos, sistema espaldera sencilla sobre camas elevadas, con fertirriego (sector A) y fertilización edáfica (sector B). Se evaluó; diámetro del tallo, longitud entrenudos, número de guías terciarias, inicio de floración y apertura floral, polinizadores, flores-frutos/planta, producción y estado fitosanitario.8 MDS (meses después de la siembra), el diámetro del tallo se incrementó hasta 2,45 cm en el sector A y 1,98 cm. en sector B. La longitud de entrenudos(eje vertical 2 m), fue de 14 cm y 12.5 cm en sector A y B respectivamente. Las guías terciarias (eje horizontal 3.5 m), promediaron 20.9 guías, con 65.95 flores y 24.04 frutos/planta en sector A, y 19.9 guías con 48.35 flores y 23.3 frutos/planta en sector B. La floración inició 5 MDS, en el 22.4% del sector A y 8.6% en sector B, con apertura floral entre 11:00 y 11:30 a.m., polinización entomófila por Xylocopa sp, reducida por Apis mellifera, maduración de frutos desde 40 a 48 días. La producción registrada 7 MDS, evaluando los primeros 30 días, presentó para el sector A; 90 kg con peso promedio/fruto de 152.33 g. El sector B, 83.6 kg con peso promedio/fruto de 148 g.En relación con el aspecto fitosanitario, se encontró que la enfermedad que más afectó el cultivo de maracuyá en condiciones ambientales del municipio de Arauca en la localidad de El Cairo, fue Alternaría passiflorae, registrando una incidencia máxima (IA) de 19.4% en el sector A y de 12.9% para el sector B. El ataque de alternaría redujo la producción del sector A, pues fue el primero en entrar a producción y expuso un mayor número de frutos a la enfermedad.Cladosporium herbarum registró una incidencia máxima (IC) de 41.8% y 41.9% para los sectores A y B respectivamente. El insecto plaga de mayor significancia para el cultivo fue Dione juno, sin embargo este se controló mediante aspersiones programadas de Bacillus thuringuiensis.